Seroprevalence and associated risk factors of Chlamydia abortus infection in ewes in Tunisia. (August 2020) - Mamlouk, Aymen; Guesmi, Kaouther; Ouertani, Imen; Kalthoum, Sana; Selmi, Rachid; Ben Aicha, Elhem; Bel Haj Mohamed, Bassem; Gharbi, Raja; Lachtar, Monia; Dhaouadi, Anissa; Seghaier, Chedia; Messadi, Lilia
Highlights: This is a sero-epidemiological survey of Chlamydia abortus in Tunisian ewes. Risk factors were investigated in herds with abortion problems. The overall seroprevalence rates at herd and individual level were 58 and 6.6%, respectively. Leading risk factors were the non-application of post-abortion measures, the exchange of breeding males and the manure management. Abstract: Enzootic abortion of ewes (EAE) caused by Chlamydia abortus is a disease of ruminants that results in serious economic losses in livestock industry. The zoonotic potential of the pathogen adds a public health concern on the efforts to control the disease. We report herein a cross-sectional study that was conducted during the lambing season (June and July) in Tunisia to estimate the seroprevalence of C. abortus infection in large sheep herds with abortion history. A total of 803 ewes were sampled and tested using indirect enzyme linked immunosorbent assay (iELISA). The overall apparent seroprevalence at herd and individual levels were 58 % (95 %CI = 39–74.5 %) and 6.6 % (95 %CI = 4.9–8.3 %), respectively. Significant risk factors investigated using univariate and multivariate analyses were history of infertility (OR = 5.7; 95 %CI = 3.05–10.66), the number of reproductive ewes (OR = 2.1; 95 %CI = 1.12–3.94), the control of new animals at introduction (OR = 4.35; 95 %CI = 2.46–7.68), the sharing of drinking water (OR = 2.18; 95 %CI = 1.22–3.9), the exchange of breeding males (OR = 2.56; 95 %CI = 1.003–6.54), the disposal of abortion materials without precaution (OR = 4.36; 95 %CI = 2.42–7.87), the lack of lambing barn (OR = 2.39; 95 %CI = 1.13–5.04), the non-application of hygienic post-abortion measures (OR = 10.35; 95 %CI = 5.28–20.26) and the manure management (OR = 11.35; 95 %CI = 3.26–39.48). To the best of our knowledge, this is the first sero-epidemiological survey conducted on an abortive disease in Tunisian ewes that investigated the risk factors of C. abortus infection.